Imbalance Nutrition and Changed Lifestyle are Main Risk Factors for Metabolic Syndrome, Diabetes and Cardiovascular Disease - Mahendra D. Bikkad, Suresh S. Ugle, (International Journal of Innovative Research in Medical Science, 2017)
Introduction -The metabolic syndrome is associated with prevalence and incidence of CHD, stroke. The Metabolic Syndrome is a modern day epidemic which predicts total and cardiovascular diseases (CVD) mortality; the incidence and progression of carotid atherosclerosis and sudden death independent of other cardiovascular risks. Subjects with metabolic syndrome have three-fold risk of a heart attack or stroke, two-fold risk of CVD or dying from such events, and five-fold greater risk of developing type 2 diabetes mellitus in both sexes when compared to people without it.Day by day the incidences of metabolic syndrome, diabetes and cardiovascular disease increases in urban as well as rural areas, rich and poor communities because of life style changes, imbalance nutrition and easy availability of cheap fast food. India which is considered diabetic capital of world needed to be explored in direction of insulin resistance and metabolic syndrome.With this background we decided to start a pilot project to find out the relation between visceral fat, metabolic syndrome and lipid profile to predict insulin resistance, diabetes and CVD. Materials and methods - We studied 50 healthy and 50 metabolic syndrome patients, with matched for age and body mass index. Subjects were selected from medical, paramedical staff and general public who were around 40 to 60 year of age. All subjects were belonged to the Latur district of Marathwada region. Patient belonging to group II were selected after attending medicine OPD of MIMSR Medical College, Latur and diagnosed as metabolic syndrome. Fasting blood sample were collected and blood glucose and lipid profile were determined. Results - In the control group I mean values of total cholesterol were 175.98 ± 26.14 mg %, serum triglycerides were 102.64 ± 31.13 mg %, and in the group II serum total cholesterol were 193.52 ± 46.20 mg %, triglycerides 165.28 ± 51.59 mg% and were significantly increased as compared to group I. The serum HDL-c in group II 39.89 ± 4.05 mg % were significantly decreased as compared to group I (45.43 ±3.13 mg %).Triglyceride /HDL-c ratio were significantly increased in group II as compared to group I. Conclusion - From results of this study, we conclude that dyslipidemia is a common feature of metabolic syndrome, and a large number of patients had more than one individual lipid abnormality. Evaluation of lipid profile indicates that HDL-c is decreased and triglycerides, and VLDL-c are increased in metabolic syndrome patients. Increased ratio of triglycerides/HDL-c is a feature of metabolic syndrome and a important predictor or marker of it. As metabolic syndrome, insulin resistance are reversible at this phase we can take preventive steps such as dietary modification, supplementation and exercise to achieve holistic health. The lipid profile, visceral fat as well as preventative measure are affordable or in hand and may be seriously considered before the development of end organ damage that may cause loss of life.